THE IMPACT OF OBESITY ON RESPIRATORY MUSCLE STRENGTH IN YOUNG ADULTS (CIPEEX, 2025)
Introduction: Obesity, characterized by excess body fat, affects all ages and is now a public health problem. This condition is identified by anthropometric measures such as Body Mass Index (BMI) and the waist-to-hip ratio. In addition to posing risks for chronic diseases, it contributes to changes in the musculoskeletal system. The global increase in obesity among adolescents and young adults suggests possible impairments in the pulmonary function of these individuals. Objectives: To associate the presence of obesity with respiratory muscle strength in young adults. Methodology: This is a cross-sectional observational study. The study population consists of 70 students from the Medicine course at UniEVANGÉLICA, according to the inclusion and exclusion criteria. The following were evaluated: body mass index (BMI) and respiratory muscle strength, through maximum inspiratory pressure (MIP) and maximum expiratory pressure (MEP). Results: showed that overweight youth had significantly higher values for Pimáx and predicted %Pimáx compared to eutrophic individuals, indicating that obesity is associated with greater respiratory muscle strength. Conclusion: In the study, overweight youth showed better values for Pimáx, with most within the expected range. Obesity, a global problem, increases the risk of respiratory and cardiovascular diseases, and the results help develop health strategies to mitigate these risks.
Keywords: Young Adults; obesity; respiratory muscle strength